Pengaruh Indeks Pembangunan Manusia (IPM), Jumlah Penduduk, dan Pengeluaran Konsumsi Pemerintah terhadap Produk Domestik Regional Bruto (PDRB) di Provinsi DKI Jakarta tahun 2014-2023 - Kirana Pramesti Rachmadiya; Luthfi Ibnu Tsani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of the Human Development Index (HDI), population, and government consumption expenditure on Gross Regional Domestic Product (GRDP) in the DKI Jakarta Province during the 2014-2023 period. Using a quantitative approach, panel data regression method, and fixed-effects model, the results show that these three independent variables simultaneously and partially have a positive and significant effect on GRDP. An increase in the HDI reflects improvements in the quality of human resources, which drives economic productivity. Population contributes to growth through employment and domestic consumption, while government consumption expenditure acts as a fiscal stimulus to increase aggregate demand. These findings are supported by endogenous growth theory, human capital theory, and the Keynesian approach, which emphasizes the importance of human capital and the active role of government in economic growth. The results of this study recommend that local governments strategically manage human development, population dynamics, and public spending policies to promote inclusive and sustainable economic growth.